Management & Organisational Behaviour - Mullins, Laurie J (Harlow, England Pearson Education Limited, 2010)
"This book provides a presentation of teaching cases emphasizing the positive and negative experiences on a variety of management topics, focusing on organizational behavior and leadership in Arab countries and the impact of culture in management and behavior"--
Includes bibliographical references (p. 354-356) and index.
Keywords: Management -- Arab countries -- Case studies; Organizational behavior -- Arab countries -- Case studies; Leadership -- Arab countries -- Case studies